Evaluation of immune responses of stabilised SAT2 antigens of foot-and-mouth disease in cattle - Scott, Katherine A. (2017)
Foot-and-mouth disease (FMD) vaccines with improved stability and less reliant on a cold-chain are needed to improve the longevity of immune responses elicited in animals. This is especially so for serotypes O and SAT2 which are unstable in mildly acidic pH conditions or at elevated temperatures leading to dissociation of the capsid (146S particle) and loss of immunogenicity. Previously, stabilised SAT2 viruses were generated by reverse genetic approaches and assessed in vitro and in vivo with a guinea pig trial. Here we investigated the efficacy and comparative immunological responses of two thermostable and wild-type SAT2 vaccines over 5 months followed by challenge. We assessed humoral immune responses elicited in cattle in terms of total and neutralizing antibodies and IgG1/2 isotyping; and cell-mediated responses of IFN-γ as in vitro markers of protection. Whilst there were significant differences in total and neutralizing antibodies for the vSAT2-93H group compared to other vaccinated groups after the first vaccination, there were no significant differences after the second immunization. Following intra-dermolingual challenge all vaccinated groups were fully protected as determined by the absence of generalized lesions. These results provide proof that two vaccine doses, consisting of SAT2 antigen combined with ISA206B adjuvant, administered 4–6 weeks apart were able to protect animals up to 5 months pv. Additionally, vSAT2-93Y had significantly higher levels of IFN-γ after challenge and had a lower clinical score indicative of better protection compared to other vaccinated groups and the importance of cell mediated responses and antigen stability in protection.